O ambiente organizacional do Sistema Agroindustrial da erva-mate - Diniz, Élio de Assis (2005)
The organizational ambient of the Agro Industrial System of the erva-mate in Brazil is represented in a significant way in the federal, state and municipal ambits, being Parana, Santa Catarina, Rio Grande do Sul and Mato Grosso do Sul the states of larger incidence of the erva-mate. The organizational ambient had its origin in the colonization and it has suffered adaptations with the objective of assisting the people's longings involved with the system. It is one of the requirements to give support to the organizations to maintain themselves competitive. However, the structuring should start internally. Before relating itself with the external ambient, the organization needs to make an internal evaluation and attempting itself to its basic principles, being linked to its member s common objectives, as well as to be aware that this collective action acts in a coordinate manner. Despite its importance, this ambient does not act in an isolated way, but concomitantly with others ambients not less important. These relations are treated in the approaches done to the New Institutional Economy that has also contributed in the aspects of the transactions among the economic agents, alerting about the possible events that can happen in its accomplishments. To study the organizational ervateiro ambient, it was opted for the technique of intensive direct observation, using the standardized interview. Lined in the obtained data with the empiric research, the ambient had its structure characterized in way to supply all the links that are part of the Agro Industrial System of the erva-mate. They have also showed that this structure is not acting in all its potential. Problems were detected that if they were not treated with the due attention, they can put all the system in risk. The damages would be considerable because of the amount of municipal districts, rural properties, companies and workers involved with the system.